Manajemen Strategi dan Kompetensi Profesional dalam Pencapaian Akreditasi Sekolah (Studi Komparatif SMPN 6 Permata dan SMP Terpadu Semayoen Nusantara) - Albar, Albar; Suhayria, Suhayria (Idarah (Jurnal Pendidikan dan Kependidikan), 2021)
Accreditation as a form of guarantee quality of education This study will discuss strategies to improve accreditation at SMPN 6 Permata and SMP Terpadu Semayoen Nusantara. The purpose of this study was to determine the strategic management carried out by the Principal in Improving School Accreditation. This study uses a qualitative method with a case study technique which is analyzed through a comparative study. Data collection techniques through interviews, observations and documentation of informants came from the Principal and the Teacher Council. The results showed that accreditation was carried out through a comprehensive assessment process referring to the SNP. Meanwhile, SMPN 6 Permata received a C accreditation while SMP Terpadu Semayoen received a B. The two schools have different characteristics of accreditation management, SMPN refers to professional values  while SMP Terpadu Semayoen refers to systems theory in the form of strategic management implementation. This research has social implications for public accountability.